Effectiveness of a Collaborative Training Model Based on Religious Moderation, Nutrition, and Mental Health on Early Childhood Parenting Practices - Ni Luh Ika Windayani; Ni Wayan Risna Dewi; Ni Putu Widyasanti (International Journal of Elementary Education, 2025)
Early childhood education and care (ECEC) practices continue to face challenges related to low levels of nutrition literacy, limited awareness of mental health, and weak moderate communication among teachers, parents, and supporting community members. This study aimed to analyze the effectiveness of a collaborative training model integrating religious moderation, nutrition, and mental health in improving parenting practices and learning management in early childhood education. The study employed an evaluative mixed-methods design with a pre–post approach. The participants consisted of 30 individuals, including early childhood teachers, parents, and community health cadres in Cempaga Village, Banjar District, Buleleng Regency, Bali. Quantitative data were collected using questionnaires on nutrition literacy and mental health awareness, while qualitative data were obtained through participatory observation, semi-structured interviews, and focus group discussions. Data analysis was conducted using descriptive statistics and thematic analysis. The results indicated a 70% increase in nutrition literacy and a 72% increase in mental health awareness following the implementation of the training. In addition, the findings revealed strengthened practices of moderate communication, supportive parenting, and cross-stakeholder collaboration. These results confirm that the collaborative training model is effective in strengthening a community-based Holistic-Integrative ECEC ecosystem and contributes to comprehensive early childhood development.